LITERASI MATEMATIKA SISWA DALAM MENYELESAIKAN MASALAH OPEN ENDED DITINJAU DARI DISPOSISI MATEMATIS - Cindy Kartika Sari; Nonik Indrawatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical literacy is a critical 21st-century competency that can be developed through open-ended problem-solving. Students’ success in solving mathematical problems is related to their mathematical dispositions. Mathematical literacy encompasses three indicators: formulate, employ, and interpret. The purpose of this study is to describe students’ mathematical literacy in solving open-ended problems as viewed from the perspective of mathematical disposition. This study employed a qualitative case study approach with three ninth-grade students as subjects, who had high, moderate, and low mathematical dispositions. Data were collected through tests, questionnaires, and interviews. The results showed that students with high mathematical dispositions were able to meet all indicators of mathematical literacy—formulate, employ, and interpret—and provided two appropriate answers; however, they were not yet optimal in evaluating alternative answers based on the problem context. Furthermore, students with moderate mathematical disposition were able to meet only the “formulate” and “employ” indicators of mathematical literacy, but they obtained one correct answer. Finally, students with low mathematical disposition were only able to meet the “formulate” indicator of mathematical literacy and were not yet able to apply the appropriate mathematical concepts, so they did not obtain any correct answers.